Breast reconstruction with the pedicled transverse rectus abdominis myocutaneous flap (TRAM) – a study of 30 menopausal women - Westfal, Bogusław; Baklińska, Magdalena; Faflik, Marcin; Zadrożny, Marek (Menopause Review/Przegląd Menopauzalny, 2004)
Objective: Reconstructive surgery is the integral part of modern breast cancer therapy. The aim of this study was to evaluate the postoperative complications and the cosmetic outcome after the pedicled TRAM breast reconstructions. Material and methods: 30 mastectomized women underwent the pedicled transverse rectus abdominis myocutaneous (TRAM) reconstructions in the period between 2001 and 2003. The local and general postoperative complications, the early and long-term cosmetic results were assessed. Results: Partial flap necrosis was the most common complication (13.3%) while the abdominal wall deformity was the most important one. The satisfactory long-term cosmetic outcome was achieved in 80% cases. Conclusion: The pedicled TRAM procedure is safe and satisfactory method of breast reconstruction surgery.